Coloured Petri net for modelling and improving emergency department based on the simulation model. (2019) - Derni, Oussama; Boufera, Fatma; Khelfi, Mohamed Faycal
Emergency department (ED) is one of the most complex systems, due to its unstable environment and the stochastic characteristics of patient flows, pathologies, and limited resources, which lead to a long waiting time. Effective management of patient flows for 'ED' services has become a critical matter for most hospital supervisors. Many authors have tried to solve those issues based on different methodologies, with shared aims represented in the optimisation of patient care, by minimising patient waiting time at different levels in 'ED'. Modern studies mainly focus on limiting these issues by proposing a solution based on extending 'ED' resources. The case study was realised at the 'ED' of the hospital Chalabi Abdelkader, Mascara, Algeria. Then, the system was modelled by a coloured Petri net framework. Afterward, we performed simulations of numerous improvement scenarios. As a result, patient waiting times encountered in 'ED' were reduced, thus patient length of stay.